2010
DOI: 10.1111/j.1469-185x.2009.00095.x
|View full text |Cite
|
Sign up to set email alerts
|

A unifying explanation for diverse metabolic scaling in animals and plants

Abstract: The scaling of metabolic rate with body mass has long been a controversial topic. Some workers have claimed that the slope of log-log metabolic scaling relationships typically obeys a universal 3/4-power law resulting from the geometry of resource-transport networks. Others have attempted to explain the broad diversity of metabolic scaling relationships. Although several potentially useful models have been proposed, at present none successfully predicts the entire range of scaling relationships seen among both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
707
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(755 citation statements)
references
References 252 publications
(566 reference statements)
44
707
3
1
Order By: Relevance
“…The handling times were expected to follow À 2 3 to 21 power-law relationships with consumer mass [38,45,46]. We found that only half of the groups tested fall into this range, whereas the others were systematically higher.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The handling times were expected to follow À 2 3 to 21 power-law relationships with consumer mass [38,45,46]. We found that only half of the groups tested fall into this range, whereas the others were systematically higher.…”
Section: Discussionmentioning
confidence: 72%
“…Besides the Metabolic Theory of Ecology, other frameworks invoke more flexible theories that predict exponents from 0.66 to 1 for metabolic rates [45,46], leading to a continuum of expectations for the handling time scaling in the range from 20.66 to 21.…”
Section: ð1:3þmentioning
confidence: 99%
“…Glazier [37] and Killen et al [38] suggest that metabolic scalings not only are influenced by temperature and body mass, but that these scalings can be affected by the activity level and ecology of organisms. Glazier [37] has suggested that depending on the activity level of an animal, the scaling exponent can vary from 0.67 to 1; therefore, as metabolic (activity) level increases, the scaling exponent decreases from 1 to 0.67 and then starts to return to 1. This U-shaped relationship reflects an increase in metabolic rate from low resting rates to active rates.…”
Section: Discussionmentioning
confidence: 99%
“…Temperature dependence of metabolic rates has been taken into account but the scaling exponents for fish, amphibians, reptiles, and mammals remained significantly heterogeneous after normalization to a temperature of 388C [17]. Eventually, Galzier [18] made an attempt to derive a unifying explanation for differences in metabolic rate scaling by broadening the focus of the analyses from considering average tendencies to understanding the variation between extreme boundary limits and from considering primarily internal factors like body design to explaining the influence of both, internal and external (ecological) factors. The inclusion of extreme situations, like sleep and in particular hibernation, suggests an interesting systematic extension of the ranges of scaling exponents at metabolic levels between the extremes of minimal and MMRs, where demand is much smaller than supply and demand is much larger than supply, respectively: The scaling exponent is supposed to be a 5 1 in the two limits and smaller in between.…”
Section: O M P L E X I T Ymentioning
confidence: 99%